Comparison of Quality of Life For Breast Conserving Surgery And Mastectomy In Early Stage Breast Cancer In Breast Cancer Survivors Community - Dian Ibnu Wahid; Kristanto Yuli Yarsa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Breast cancer surgery can impact patients psychologically as well as organically, which can manifest as Quality of life (QOL). Thirty patients, the age ranged between 25 and 60 years and the mean age 41 years. Twenty seven patients have married, a widow, and two unmarried. There was not found a difference in health related quality of life. No differences were seen in level of pain, skin sensitivity and related problems in surgical area. Woman in mastectomy group reported stastitically more problem with their body image. Beyond that, they also have a complaint about the feelings of sexual attractiveness than woman in breast conserving surgery (BCS). Women undergoing breast conserving surgery experience more positive outcomes than women undergoing mastectomy. Women in the mastectomy groups also reported experiencing more physical problems related to their surgery. The score of CES-D is above 16 both breast conserving surgery’s group and mastectomy’s groups. Higher scores are associated with more symptoms. There were also no differences seen among them as measured by the MOS, four main poins consists of emotional support, real support, affection support and good social interactions. There were also no differences seen among them as measured by the RDAS consists of three aspects (concensus, satisfaction, cohession). This can happen because the doctors give well support and education to all patients. Despite, the patients, their families, their partners also give support each other. The women sight of their body images was considered making well social interaction. Most of the study showed the declining of social interactions after the surgery. This happened beacuse they were apprehensive about rejection in social life.